TRANSPORTATION STRATEGY DEVELOPMENT FOR OPTIMUM COAL MINING: A CASE STUDY OF BLOK-D MINING PROJECT PT. XYZ (The Indonesian Journal of Business Administration, 2021)
Blok-D included in PT.XYZ concession is blessed with large coal resources and has the potential to be the main pillars of the company's future sustainability. The low calorific value of the coal resources and their locations are believed to erode the value of the mining project. Evaluate whether mining Blok-D is a relevant strategy for the Company, and then the development of the transportation strategy is a must before the mining project started. Selected transportation strategy is according to those who can provide a return on investment at equal or higher than the shareholder expectation.The increase in demand for coal by India and other countries in Asia was one of the reasons why the coal industry still had a strong appeal. Supported by its several competitive advantages, PT.XYZ has the advantage to grow the business by doing Blok-D mining. Assessment of the financial aspect is a must since it becomes the major challenge for transportation strategy development.Cost leadership is a suitable competitive strategy for the Company according to the analysis of the Company’s capabilities and competitive advantages. SWOT and TOWS approach shows that mining Blok-D is an inline strategy with the company’s corporate strategy. There are 6 (sixth) alternatives solutions for the transportation strategy, which are distinguished by the location of the barge loading facilities and the land coal transport method. The DCF financial model indicates that Alternative B1.2 provides the highest project value. The sensitivity analysis shows that the coal price followed by the OPEX becomes the most sensitive input variable for the project value. Monte Carlo analysis results show that Alternative B1.2 is viable to be executed since it gives an expected NPV of 333.47 million USD and an IRR of 65.4% which is higher than 11.96% as the required rate of return (WACC). Based on the analysis result, PT.XYZ is recommended to do the Blok-D mining projects with Alternative B1.2 as the transportation strategy.Keywords: Transportation strategy, business strategy, coal mining, investment analysis, DCF model, Monte Carlo analysis.